Media Pembelajaran PPKn Pada Anak Tunarungu Di SMP Berkebutuhan Khusus (Studi Kasus SMP-LB Negeri Surakarta Tahun Ajaran 2015/2016) - Hariyanto, Agus (2016)
LEARNING MEDIA PPKN ON DEAF CHILDDREN THE JUNIOR HIGH IN NEED SPECIAL (A CASE STUDY OF SMP NEGERI SURAKARTA ACADEMIC YEAR 2015/2016). Agus Hariyanto and Sri Arfiah Civics And Citizenship, Faculty Of Teacher Training And Educational Sciences, Muhammadiyah University Of Surakarta agus_hari14@ymail.com ABSTRACT The purpose of this research is to know the medium used in the proceses of learning of civics and citizenships on deaf children in junior high state of Surakarta-LB academic year 2015/2016. Learning media being used I media images and media char. This research is qualitative research, with data collection techniques used are observation, interview an reviewing documentation. The validity of the data using triangulation triangulation techniques and data sources data collection. Data analiysis was done with the interactive analysis model that includes data collection, data reduction, the presentation of data, and the withdrawal of the conclusion. The results of this research show that: 1). Learning media is a tool in the form of physical and non physical who deliberately used as an intermediary between teachers and students in understanding the subject matter in order to more effectively and efficiently. 2). Implementation of the medium of instruction in deaf children hafe advantages and disadvantages. Pros and cons are obtained through observations conducted by the observer. The advantages of media images and charts that is abel to describe and clarify the subject matter. 3). The weakness of the application of media images and chart are applied less media in accordance with the conditions of the students, the students are confused understand media, and the mediaare less attractive. Keywords: Learning, Media of learning, The child is deaf, PPKn Surakarta January 2016 Penulis AGUS HARIYANTO